Renewable energy education at the university level [compact disc] - 357410 Nor Hazlinda Md. Khairi (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2003